Active and Passive Adaptation of Floating Houses (Rumah Lanting) to the Tides of the Melawi River in West Kalimantan, Indonesia - Putro, Jawas Dwijo; Zain, Zairin (Geographica Pannonica, 2021)
Floating houses (Rumah Lanting) are one of the settlement cultures that can be found in most river streams in Kalimantan. The floating houses are different from other houses. Rumah Lanting is a mitigation-proof house to respond to the risk of disasters that occur in a traditional settlement in West Kalimantan. These types of houses are dwelling with a structure that can adapt to environmental conditions, including natural disasters. The natural phenomena that eventuate in traditional settlements in West Kalimantan are the tides in the river that routinely occur during the rainy season (as flood) and dry season (as ebb) during the year. Floating houses or RumahLanting are one of the settlement cultures found in most river streams in Kalimantan and are observed to be different from several other houses in the area. They are mitigation-proof houses designed to respond to the risk of disasters usually experienced in the traditional settlements of West Kalimantan. Their structures have the ability to adapt to environmental conditions including natural disasters such as the river tides routinely experienced as a flood during the rainy season and as ebb in the dry season. This study aimed to identify the human-adaptation process existing in these floating houses through direct observation for two years during the dry and rainy seasons as well as in-depth interviews conducted with occupants of these buildings. The adaptation processes identified include the active and passive adaptation of the dwellers. The active aspect was observed from the behavior of occupants in accommodating the occurrence of disaster in the surrounding environment while the passive was identified as the physical changes implemented in the building to mitigate the disaster. The focus of this research was on some dwellings on the river banks settlement in the Melawi River near Sintang Regency of West Kalimantan Province and a qualitative approach with a case study was implemented. The samples were determined through a non-probability approach in the form of a purposive sampling method based on certain selected criteria which included the previous experience of ebb and flow of river water in the RumahLanting. The results showed the existence of active and passive adaptations for the dwellers of the floating houses in West Kalimantan. The active aspect observed involves the behavior of the occupants in adapting to natural disasters with the focus on the changes in the activity patterns, territory, and privacy. Meanwhile, the passive aspect showed some modifications in the architectural elements of the building such as the position, orientation, access, and function. The results of this study explained that active and passive adaptations of dwellers were found in the floating house in West Kalimantan. Active adaptation involves the behavior of the occupants in adapting to natural disasters. The changes that occur are in the forms of activity patterns, territory, and privacy. Meanwhile, the changes in the physical appearance of the building were indicated as the passive adaptation of the occupants. The adaptation of the dwellers appears as the activities to modified some architectural elements in Rumah Lanting, such as position, orientation, access, and function.